2001
DOI: 10.1079/bjn2001388
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and cognitive impairment in the elderly

Abstract: As the number of older people is growing rapidly worldwide and the fact that elderly people are also apparently living longer, dementia, the most common cause of cognitive impairment is getting to be a greater public health problem. Nutrition plays a role in the ageing process, but there is still a lack of knowledge about nutrition-related risk factors in cognitive impairment. Research in this area has been intensive during the last decade, and results indicate that subclinical deficiency in essential nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 89 publications
2
71
0
1
Order By: Relevance
“…15 Genetic factors also seem to affect homocysteine levels. [16][17][18][19] Elevated levels of homocysteine can be caused by mutations in enzymes involved in homocysteine metabolism,whichgivedysfunctionalenzymes, for example, the single-nucleotide polymorphism at position 677 in the methylenetetrahydrofolate reductase (MTHFR) gene for MTHFR. 17 Methylenetetrahydrofolate reductase is a key enzyme in homocysteine metabolism.…”
Section: Omocysteine Has Beenmentioning
confidence: 99%
“…15 Genetic factors also seem to affect homocysteine levels. [16][17][18][19] Elevated levels of homocysteine can be caused by mutations in enzymes involved in homocysteine metabolism,whichgivedysfunctionalenzymes, for example, the single-nucleotide polymorphism at position 677 in the methylenetetrahydrofolate reductase (MTHFR) gene for MTHFR. 17 Methylenetetrahydrofolate reductase is a key enzyme in homocysteine metabolism.…”
Section: Omocysteine Has Beenmentioning
confidence: 99%
“…A better understanding of dietary factors that contribute to the maintenance of cognitive ability is thus of high priority (4) . The importance of prospective studies of specifically long duration, which would include subjects whose diet was monitored long before cognitive assessment, has previously been stressed (5) . Using longitudinal data from the 'Etude Epidémio-logique de Femmes de la Mutuelle Générale de l'Education Nationale' (Epidemiological Study of Women of MGEN) (E3N) study, we examined the associations between previous usual diet and age-related cognitive impairment.…”
mentioning
confidence: 99%
“…In humans, a number of epidemiological case -control and prospective studies analysed the association between nutrition, particularly fatty acids and antioxidant molecules (vitamins A, E and C, b-carotene and polyphenols) and cognition and risk of stroke (49) . In fact, intensive research has indicated that subclinical deficiencies of essential nutrients such as antioxidants (vitamins C and E), b-carotene, vitamin B 12 , vitamin B 6 and folate in combination with nutrition-related disorders, such as hypercholesterolaemia, hypertriacylglycerolaemia, hypertension and diabetes, are important risk factors associated with cognitive impairment (8) . Current scientific evidence also suggests a protective role for fruits and vegetables in the prevention of CHD, and evidence is accumulating towards a protective role in stroke (22,42,50 -52) .…”
mentioning
confidence: 99%